Culture and economic development in Africa - opportunities and challenges - John E. Kuada (African Governance and Development Institute (AGDI), 2020)
This paper forwards the view that some aspects of African culture enhance economic development on the continent while other aspects tend to constrain development. By drawing on the extant literature on culture and development, the paper discusses the manner in which economic activities are organised in Sub-Saharan African countries and the impact of these processes on their overall development. We argue that insight into the development-constraining attributes of African culture will help policymakers and business people design policies and strategies that will improve the overall performance of African economies.
Keywords: 330; Culture; economic development; business development; entrepreneurship; Africa